Potentiometric Membrane Sensors for Determination of Memantine Hydrochloride and Pramipexole Dihydrochloride Monohydrate - Merey,Hanan A. (2012)
Five solid membrane sensors responsive to memantine hydrochloride (MEM) and pramipexole dihydrochloride monohydrate (PXL) are described for simple and fast determination of these drugs in pharmaceutical preparation and human plasma. The first and the second sensors are based on the formation of an ion association complex between MEM as a cationic drug with Na tetra phenyl borate and ammonium reineckate (as anionic exchanger), respectively. The third sensor is based on the formation of an ion association complex between PXL with ammonium reineckate. The produced electroactive material is dispersed in PVC matrix. While the other fourth and fifth sensors are based on using functionalized lipophilic cyclodextrin derivative (2-hydroxypropyl-β-cyclodextrin) as sensor ionophore for the determination of MEM and PXL. The performance characteristics of these sensors-evaluated according to IUPAC recommendations-reveal fast, stable and near Nernstian response for 1 \D7 10-4 - 1 \D7 10-1 M and 1 \D7 10-6 - 1 \D7 10-2 M for (MEM) and (PXL), respectively. Many inorganic and organic substances such as drug excipients and diluents normally used in drug formulations do not interfere with drugs response. Statistical comparison between the results obtained by applying the proposed potentiometric method for the determination of the (MEM) and (PXL) in their pure powder forms and those obtained by applying the reported methods was done and no significant difference was found at p = 0.05. Validation of the method according to ICH guidelines shows the suitability of the sensors for quality control analysis of the cited drugs in pharmaceutical formulations and human plasma. The proposed sensors can also be used as a detector for HPLC.